Intellectual capital efficiency and firm performance in Malaysia: the effect of government ownership - Nurul Syamimi Zulkifli; Zaleha Abdul Shukor; Mara Ridhuan Che Abdul Rahman (Penerbit Universiti Kebangsaan Malaysia, 2017)
In the era of digital information, intellectual capital becomes more important to firms because the economic environment throughout the world continuously focused on the existence of knowledge capital in the firms to ensure firms’ survival. However, the existence of firms’ investment in intellectual capital is not clear because it is reported as an expense rather than asset. This situation makes the efficiency of intellectual capital investments vague which can jeopardize firms’performance and value. However this weakness could be overcome with a reliable governance in the firms. The objective of this study is to investigate the moderating effect of government ownership (a characteristic of corporate governance) in the association between the efficiency of intellectual capital and firm performance. Government ownership has always been seen by investors as controversial especially when the government seems to always taking advantage of firms’ wealth. This study utilised a sample of 1,048 firm-years data from financial statements of firms listed on the main market of Bursa Malaysia for years 2012 through 2014. Findings shows a positive association between intellectual capital efficiency and firm performance. However the existence of government ownership weakens the association. Findings support the grabbing hand theory which argues that government ownership is seen as negative by stakeholders due to only taking advantage and not enhancing the existence of intellectual capital in firms. Findings show that investors still need to be alert if they want to invest in firms owned by the government in Malaysia. Nevertheless, the findings could also assist the government as owners to listed firms to improve their reputation in order to be seen as the entity that would help elevate firms’ performance which could eventually assist to heighten the capital market and economy of Malaysia.